Prognostic factors for survival in patients with advanced cholangiocarcinoma treated with percutaneous transhepatic drainage - Tomas Rohan; Barbora Cechova; Peter Matkulcik; Matej Straka; Jan Zavadil; Michal Eid; Michal Uher; Marek Dostal; Tomas Andrasina (Scientific Reports)
Abstract Biliary drainage is then one of the necessary procedures to help patients suffering from icterus to reduce serum bilirubin levels and relieve symptoms. The aim of this study was identifying risk factors for survival in patients with cholangiocarcinoma (CCA) treated with percutaneous transhepatic biliary drainage (PTBD) and to develop a simple scoring system predicting survival from PTBD insertion. This single-centre retrospective study included 175 consecutive patients undergoing PTBD for extrahepatic CCA (perihilar and distal). Prognostic factors affecting survival of patients with CCA treated with PTBD were analysed. A multivariate analysis showed that mass forming tumor with mass larger than 5 cm and presence of metastasis at the time of PTBD served as a negative prognostic factor (p = 0.002), better survival was associated with lower preprocedural bilirubin and lower CRP (p = 0.003). Multivariate analysis identified two significant risk factors for 3-month mortality: mass-forming tumors and bilirubin levels exceeding 185 µmol/L. A simple scoring system was developed to predict 3-month mortality after PTBD in patients with advanced CCA, demonstrating 86.3% negative predictive value and 43.2% positive predictive value.